What do we have to know about Cystic Lung Diseases? - Sánchez Díaz C; Díaz-Lobato S (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
Introduction: Cystic lung diseases are a heterogeneous group of pathologies which differential diagnosis can be complicated[1]. We are going to comment some aspects that we should know about cystic lung diseases to facilitate a better understanding and clinical management of these entities.